ANALISIS PERBANDINGAN KINERJA REKSA DANA SYARIAH DAN KINERJA REKSA DANA KONVENSIONAL DENGAN METODE SHARPE, TREYNOR DAN JENSEN - Azizatur Rahmah (Program Pascasarjana UIN Sumatera Utara, 2016)
This thesis discusses about the Comparation of Performance and Risk between Islamic Mutual Funds with Conventional Mutual Funds where Islamic mutual funds differ fundamentally from conventional mutual funds. The period of this research is from January 1st , 2013 until December 31th, 2015 and this research uses Sharpe, Treynor and Jensen model for data processing. The result of data processing and analyzing from this research, overall the performance of the entire mutual funds are still not optimal. However, when compared in terms of performance and risk among Islamic mutual funds with conventional mutual funds, conventional mutual funds have better performance compared to Islamic mutual funds. For the risk, with Sharpe method, conventional mutual funds have a lower total risk than Islamic mutual funds. For the treynor, conventional mutual funds have a lower total risk than islamic mutual funds. For the Jensen islamic mutual funds have a lower total risk than conventional mutual funds. The third method of Sharpe, Treynor and Jensen performance superior to conventional mutual funds .